2020
DOI: 10.1007/s11661-020-06045-z
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Phase Transformations Involving (Nb,Mo)2CrB2 Borides and (Nb,Ti)2CS Carbosulfides at the Grain Boundaries of Superalloy Inconel 718

Abstract: The present paper studied the solid-state phase transformations occurring at the grain boundaries of a conventional cast-and-wrought alloy within the chemical specifications of superalloy Inconel 718. These phase transformations involved the precipitation of (Nb,Mo) 2 CrB 2 borides and (Nb,Ti) 2 CS carbosulfides, which are usually phases rather associated to solidification phenomena than to solid-state phase precipitation in superalloy Inconel 718. The study started from a material solution-treated above the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Be fore oxidation the material had been solution treated at 1050 °C (thus above the solvus) and that for several durations. A previous work [14] had shown that this material exhibited several phases at grain boundaries: (Nb,Mo) 2 CrB 2 borides (which had precipitated during a prior subsolvus treatment), eventually some residual precipitates, and secondary (Nb,Ti)C carbides. But because the material had been pre viously solution treated at high temperature, large amounts of chemical species were still in solution in the microstructure.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Be fore oxidation the material had been solution treated at 1050 °C (thus above the solvus) and that for several durations. A previous work [14] had shown that this material exhibited several phases at grain boundaries: (Nb,Mo) 2 CrB 2 borides (which had precipitated during a prior subsolvus treatment), eventually some residual precipitates, and secondary (Nb,Ti)C carbides. But because the material had been pre viously solution treated at high temperature, large amounts of chemical species were still in solution in the microstructure.…”
Section: Introductionmentioning
confidence: 82%
“…More precisely, four types of samples corresponding to four durations of solution treatment were oxidized: ST 10 (solution treated for 10 min), ST 30 (solution treated for 30 min), ST 60 (solution treated for 60 min) and ST 120 (solution treated for 120 min). According to the study presented in [14] , the ST 10 type samples mainly exhibited precipitates and (Nb,Mo) 2 CrB 2 borides at grain boundaries ( Fig. 1.…”
Section: Materials and Microstructurementioning
confidence: 90%
See 3 more Smart Citations